2013
DOI: 10.9778/cmajo.20120017
|View full text |Cite
|
Sign up to set email alerts
|

The consumption of alcohol mixed with energy drinks: prevalence and key correlates among Canadian high school students

Abstract: Research CMAJ OPENT he consumption of energy drinks, beverages that contain moderate to high concentrations of caffeine as well as taurine, herbal supplements, and sugar or sweeteners, has risen steadily in the last decade, 1 with sales surpassing those of many other nonalcoholic beverages in North America.2,3 These beverages have become particularly popular among youth and young adults owing to their purported stimulant effects and ability to increase alertness and enhance mental and physical energy. 1,[4][5]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 40 publications
9
41
0
Order By: Relevance
“…Energy drinks, because of their high caffeine content, are increasingly being mixed with alcohol, often in an attempt to reduce feelings of alcohol intoxication. 11,29 There is also evidence of mixing energy drinks with cannabis and prescription drugs -13% of overall visits to US emergency departments that related to energy drinks involved the mixing of energy drinks with alcohol and 10% involved mixing with illicit drugs such as cannabis. 16 Current findings that high sensation-seeking (reported by 16% of respondents) and recent injuries (reported by 42%) are associated with energy drink consumption are consistent with research on college students that found greater jock identity and risk-taking behaviours among individuals who consume energy drinks.…”
Section: Discussionmentioning
confidence: 99%
“…Energy drinks, because of their high caffeine content, are increasingly being mixed with alcohol, often in an attempt to reduce feelings of alcohol intoxication. 11,29 There is also evidence of mixing energy drinks with cannabis and prescription drugs -13% of overall visits to US emergency departments that related to energy drinks involved the mixing of energy drinks with alcohol and 10% involved mixing with illicit drugs such as cannabis. 16 Current findings that high sensation-seeking (reported by 16% of respondents) and recent injuries (reported by 42%) are associated with energy drink consumption are consistent with research on college students that found greater jock identity and risk-taking behaviours among individuals who consume energy drinks.…”
Section: Discussionmentioning
confidence: 99%
“…Lose weight, Gain weight, Stay the same weight, I am not trying to do anything about my weight". Spending money, associated with AmED use in a previous Canadian study, 22 presumably because the higher cost of these drinks may serve as a barrier to some youth, was assessed using the question, "About how much money do you usually get each week to spend on yourself or to save?" with responses recoded as 0 = $0, 1 = $1-$20, 2 = $21-$100, 3 = >$100, and 4 = Not stated (Missing/Don't know).…”
Section: Socio-demographic Variablesmentioning
confidence: 99%
“…Intensity of alcohol use was strongly associated with energy drink use: students reporting any level of alcohol use were more likely to use than those who did not drink at all, and the odds increased with increasing intensity of alcohol use. When two-way interactions between sex and the other covariates were tested (individually) in the model for any use of energy drinks, several interactions were significant: sex with age (F (1,22,778) = 14.4, p = 0.0001), spending money (F (4, 22,775) = 4.2, p = 0.002) and weight efforts (F (3,22,776) = 9.3, p ≤ 0.0001), and the interaction of sex and race was of borderline significance (F (5, 22,774) = 2.9, p = 0.012). While any use of CEDs increased consistently with age among males, a contrasting pattern was observed among females: use was highest among the youngest students and decreased with age up until age 17; those aged 18 and older also had high use.…”
Section: Any Energy Drink Usementioning
confidence: 99%
See 1 more Smart Citation
“…Withal, another study showed that Canadian college students who reported drinking AmEDs (alcohol-mixed energy drinks), were significantly inclined to cigarette smoking, heavy drinking, and marijuana use [99,46], suggesting that AmED, as well as ED (energy drinks) consumption, is another expression of a high-risk behavior lifestyle [46], such as marijuana and alcohol use.…”
Section: Alcohol and Other Drugsmentioning
confidence: 99%